Analysis of Women Entrepreneurship in Autonomous Region in Muslim Mindanao - Ali, Emraida Calim (International Journal of Management Excellence (ISSN: 2292-1648), 2020)
This is a quantitative study conducted to analyze the factors that influence the extent of women entrepreneurship in the Autonomous Region in Muslim Mindanao. The descriptive-correlation research design was used to execute the research and analyze the data. The respondents were the selected women entrepreneurs in the provinces of Maguindanao, Lanao del Sur, Basilan, Sulu and Tawi-tawi. A modified research questionnaire was used in this study as the main data-gathering instrument. Data were analyzed using the frequency, percentage, mean, multiple regression analysis, and hierarchical multiple regression. The personal entrepreneurial competency, presence of entrepreneurial role model, government programs and interventions, motivation, entrepreneurial environment, and cultural orientations were studied whether they influence the extent of women entrepreneurship in terms of involvement in the four phases of entrepreneurial activity: searching; planning; marshalling; and implementing. Moreover, age and educational attainment were studied whether they offer significant contingent effect on the relationship of the dependent and independent variables. Results of the study revealed that significant predictors are the personal entrepreneurial competency, government programs and interventions, motivation, and entrepreneurial environment. And the best predictor of women entrepreneurship is government programs and interventions. Moreover, the age and educational attainment have no significant contingent effect on the relationship of the dependent and independent variables.